Técnicas de projeto para o reator eletrônico auto-oscilante empregando ferramentas de controle - Seidel, Álysson Raniere (2004)
This work presents a design methodology and analyss of the selfoscillating electronic ballast used in fluorescent lamps. The self-oscillating electronic ballast is represented as a control system with a nonlinear behavior. In this representation the describing function method and extended Nyquist stability criterion are used to determine the circuit parameters. Besides, the time domain analysis is performed by the differential equations that describe the circuit behaviour. From the analysis carried out it is possible to get some interesting simple alternatives for the self-oscillating electronic ballast applications, such as: dimming capability, power factor correction, and lamp current creast factor correction. It allows increasing the circuit applications whithout compromising the simplicity, reliability, and low cost that characterizes the self-oscillating electronic ballast. Experimental and simulation results are presented to confirm the performance and to validate the analysis, design, and applications presented using the self-oscillating electronic ballast